ETHNIC CHARACTERISTICS OF TRADITIONAL EMBROIDERY AMONG THE NATIONS OF FERGANA VALLEY (British Journal of Global Ecology and Sustainable Development, 2022)
The article discusses the fact that the culture of embroidery is part of Uzbek ancient Applied Art, women's hopes and dreams, aesthetic world, worldview, expression of love through colorful images, as well as the fact that embroidery has a centuries-old history.